Using Spatial Autocorrelation for identification of demographic patterns of Functional Urban Areas in Poland - Kurek, Sławomir; Wójtowicz, Mirosław; Gałka, Jadwiga (Bulletin of Geography. Socio-economic Series, 2021)
Functional Urban Areas (FUAs) leads to a better knowledge of urban spatial organisation, which may play a significant role in regional policy making and may be helpful in understanding the connection between urbanisation and demographic development. An explanation of population change in urban regions can be associated the second demographic transition comprising fertility decline below replacement level and postponement of births. This paper deals with a typology of FUAs selected on the basis of methods of spatial autocorrelation. The aim of the article is to identify the spatial relationships occurring in Urban Functional Areas in Poland in terms of selected demographic variables using spatial autocorrelation methods. Spatial methods play an increasingly important role in contemporary socio-demographic research. In order to identify spatial systems Global Moran Statistics and the Local Indicators of Spatial Association (LISA) including Local Moran statistics as well as Getis-Ord Gi* statistics were used. The article finds that spatial autocorrelation methods (global and local Moran’s I statistic, and the Getis-Ord Gi* method) identified the global and local spatial relationships for existing functional urban areas representing different demographic variables. Spatial autocorrelation methods can be useful in an analysis of demographic variables including changes in time. It can be useful in analysis of spatial clusters of areas undergoing second demographic transition. This paper demonstrates areas that are characterized by similar or different values of the studied variables, which allows monitoring and spatial planning of the functional urban areas.